Fractures of Orbital Floor (Statistics) - D. Hrušák; J. Jambura; L. Hauer (Czech Dental Chamber, 2010)
Orbital floor fractures of the blow-out type are not the most frequent in traumatology of orofacial region, but the consequences (particularly persisting diplopia) may seriously handicap the patient in personal and professional life. Opinions of the correct mode of therapy of this injury have been changing throughout the history. New recommendations concerning indications for surgical or conservative treatment arrive all the time as well as questions of the correct time for intervention. In their retrospective study the authors deal with a statistical evaluation of the therapy of 63 patients with blow-out fractures, which was applied in the period of January 2001 through March 2010 at the Stomatology Clinic of Medical Faculty, Charles University and Teaching Hospital at Pilsen. In the present group were followed the age, sex, etiology of the injury, and in surgically treated patients also the used accesta the orbit and the implant types. The results of treatment (conservative/surgical) were then evaluated in view of the lasting diplopia.